The Borg CR-10 scale is suitable to quantify aerobic exercise intensity in women with fibromyalgia syndrome (Fisioterapia e Pesquisa, 2017)
Patients with Fibromyalgia syndrome (FMS) report higher ratings of perceived exertion (RPE) compared to healthy individuals for the same exercise intensity; however, to our knowledge, no studies have evaluated RPE at the ventilatory anaerobic threshold (VAT) for this population. This study aimed to assess RPE using the Borg CR-10 scale during a cardiopulmonary exercise test (CPET) in women with FMS. Twenty-four women with FMS and twenty healthy control subjects (HC) voluntarily participated in this study. Near the end of every 1-minute period during CPET, subjects were asked to report their RPE for fatigue in the lower limbs (RPE-L) and dyspnea (RPE-D), respectively, according to the Borg CR-10 scale. FMS subjects showed higher RPE-L and RPE-D compared to HC subjects at free wheel and at the first load increment. However, no significant difference was observed between groups for power output. There was no significant difference between groups for RPE-L and RPE-D reported at VAT and peak CPET. However, FMS subjects showed lower power output compared to HC subjects. The present results showed that FMS subjects present higher RPE compared to HC subjects. However, RPE reported at VAT and at peak CPET was not different between groups. The Borg CR-10 scale scores obtained at VAT can be used as an additional parameter for prescribing exercise intensity in aerobic training protocols for women with FMS.